Pengaruh Pendapatan Asli Daerah dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah Tingkat II di Provinsi Jawa Timur Periode 2018 – 2022 - Clarisa Sukmaning Ati; Imam Baidlowi; Nur Ainiyah; M. Bahril Ilmiddaviq (Pusat Riset dan Inovasi Nasional, 2023)
The emergence of the Covid-19 virus in 2019 caused an economic crisis for all regions in Indonesia. So an appeal was issued to prevent the occurrence of Covid-19. However, this implementation has affected various sectors, especially the economic sector. East Java Province is one of the provinces affected by the Covid-19 pandemic, so that the economy in East Java Province has experienced a decline. The purpose of this study was to determine the effect of Regional Original Revenue and Capital Expenditures on the Financial Performance of the Level II Regional Government of East Java Province for the 2018-2022 Period. The research methodology uses a quantitative research methodology, the sample used uses saturated sampling. Data analysis in this study used descriptive statistical analysis with Patrial Least Squares (PLS) software. The results of this study are that regional original income has a significant effect on local government financial performance and capital expenditure has no significant effect on local government financial performance.